COLLECTION, PURIFICATION AND PHYTOCHEMICAL SCREENING OF A NATURAL GUM FOR ORAL CONTROLLED DRUG DELIVERY SYSTEM - Sujit Das2, Amitava Roy2Jyotirmoy Deb*1, Mrinmay Das1, Arup Das1 P. Mohonraj1, Arwan Raplang Lyngdoh*2 (Journal of Biomedical and Pharmaceutical Research, 2016)
Present study highlighted that sustained release matrix tablet of Indomethacin using gum karaya (GK) as matrix former. Various concentrations of KG used to ensure the release model. Preformulation study of Indomethacin was done initially and results directed for the further course of formulation. Based on preformulation studies different batches of tablet have been prepared by wet granulation method by using selected excipients. Granules were evaluated for various tests before being punched as tablets. Tablets were tested for weight variation, thickness, hardness and friability as per official procedure. Dissolution of batch F1 – F6 were carried out in phosphate buffer pH 6.8 media. In vitro dissolution test reveal that is dependent upon the nature and concentration of the polymer. It was concluded that F3, F5 and F6 shown best drug release profile after12 hours i.e. 92.39%, 98.54% and 93.525% respectively and the release seem to obey the Higuchi kinetic model and were finally optimized. Keywords: Higuchi Model, Gum Karaya (GK), Indomethacin, Matrix Tablet, Sustain release (SR)